Implementasi Bayani, Irfani, Burhani Terhadap Pendidikan Karakter Santri dalam Sistem Pendidikan di Pesantren - Amrullah, Muhammad Afif; B.K.P.S, Alaika Muhammad; Fawaid, Imam; Alfaruq, Moch Ishaq (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2022)
Regarding theiproblem of life, moral degradation is often heard in the body of the next generation of the nation. Starting from small children, adults, to the erderly. Today’s formal education tens to present learning materials based on intellectual intelligence, while in everyday life emotional intelligence and spiritual intelligence are needed. With the concept of marginal understanding, there will be a gap because someone's understanding is cognitively different. Especially now that it is supported by technological advances that are free to erode understanding of character. This then forms a character in a person because of his ability to internalize it. A person's character will experience ups and downs when theory is only used as a starting point in behavior. Through analysis Bayani, Irfani, and Burhani will describe how it is implemented in the education system. The method used is library research , in which the orientation is to examine books, manuscripts, and literature relevant to the object of research. The results of this study conclude that the education system in Islamic boarding schools is not only based on theory but habituation. The pesantren environment that brings them to study does not only apply knowledge through doctrination, but in actualization in their lives as santri. This can be seen through several phenomena that occur such as gangsters, fights between students, until narcotics are also found in young people. And this is rarely found for those who are in dormitories or from pesantren graduates. Keywords: Bayani, Irfani, Burhani, Character, Islamic Boarding School